Examining employees creativity in commercial bank of Ethiopia Woldia branches - Erstu Tarko Kassa (Journal of Innovation and Entrepreneurship, 2021)
Creativity is the ability to combine unique ideas, identifying new ways, systems and products in the organization. Creative workers in the organization can transform their organization to higher level by inventing new systems. This study tried to examine employees' creativity in the bank at commercial bank of Ethiopia Woldia branches. The researcher used an institutional-based cross-sectional design and followed a mixed research approach. The researcher applied a census method to participate in respondents from four branches, which were on duty 182 employees in commercial bank of Ethiopia. The collected data were analyzed by using multiple regression method after proving the quality of the data. The study finding revealed that autonomy, supervisors' support and role ambiguity significantly affects the creativity of employees in the workplace. The remaining variables self-efficacy and job complexity have no statistically significant effect on employees' creativity in the bank.
Keywords: 650; Employees’ creativity; Autonomy; Supervisors support; Job complexity; Role ambiguity; Self-efcacy